2021
DOI: 10.1016/j.compedu.2020.104056
|View full text |Cite
|
Sign up to set email alerts
|

Media multitasking, online vigilance and academic performance among students in three Southern African countries

Abstract: High levels of Internet-based media use is a defining feature of behaviour among university students. A growing body of evidence indicates, firstly, that their learning activities are characterised by frequent switching between academic content and online media, and, secondly, that this form of behaviour is negatively associated with academic outcomes. It is less clear, however, whether media use and media multitasking in general is associated with academic performance. In the present study we adopted an explo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
12
0
3
Order By: Relevance
“…These are, firstly, the absence of evidence about adoption and use rates of digital wellbeing applications among university students (in general and especially in developing countries), secondly, the lack of evidence for the impact of these applications on their smartphone use behaviour, thirdly, a lack of knowledge about use motivations of digital wellbeing applications, and, finally, a lack of knowledge of students' perceptions of the value of these applications in their efforts to achieve digital wellbeing. University students present an important demographic for the study of digital wellbeing due to their high levels of smartphone ownership and use (Panova et al, 2020;le Roux et al, 2021). Additionally, studies have found that students are generally aware that excessive smartphone use, particularly in learning contexts, can be negatively associated with learning and academic performance (Junco, 2012;Parry, 2017;Whelan et al, 2020).…”
Section: Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…These are, firstly, the absence of evidence about adoption and use rates of digital wellbeing applications among university students (in general and especially in developing countries), secondly, the lack of evidence for the impact of these applications on their smartphone use behaviour, thirdly, a lack of knowledge about use motivations of digital wellbeing applications, and, finally, a lack of knowledge of students' perceptions of the value of these applications in their efforts to achieve digital wellbeing. University students present an important demographic for the study of digital wellbeing due to their high levels of smartphone ownership and use (Panova et al, 2020;le Roux et al, 2021). Additionally, studies have found that students are generally aware that excessive smartphone use, particularly in learning contexts, can be negatively associated with learning and academic performance (Junco, 2012;Parry, 2017;Whelan et al, 2020).…”
Section: Current Studymentioning
confidence: 99%
“…The study involved a sample of undergraduate students at a large, research-intensive university in South Africa. Previous research shows that students at such institutions are comparable to their Western counterparts when it comes to media use (Broughton et al, 2019;Chokalingam et al, 2019;le Roux et al, 2021). Invitations to complete an online survey were emailed to all undergraduate students at the institution in mid-2020.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it is obvious that social networking is an essential element of ICTs, and that ICTs plays a role in delivering excellent humanistic services, including educational services at various levels, which may help forecast the procrastination of source employee (Chen et al, 2021;Toyama and Hayashi, 2021). Employees who spend excessive time on nonorganizational ICT activities run the danger of procrastinating, resulting in poor performance despite the organizational benefits of ICTs (le Roux et al, 2021).…”
Section: Multitasking and Procrastination Behaviormentioning
confidence: 99%
“…The psychological state of people who always want to be online is known as online vigilance (Reinecke et al, 2018). This habit is brought on by the constant use of digital gadgets, which has ramifications for a state that is constantly curious about how information spreads online (le Roux et al, 2020). This view demonstrates that each person responds differently to the allure and importance of connecting via digital technologies (Reinecke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%